Embodiment in evolution and culture - Tewes, Christian; Etzelmüller, Gregor (Mohr Siebeck, 2016)
Die Evolutionstheorie hat anthropologische Grundannahmen über die Stellung des Menschen in der Natur erschüttert. Der Darwinischen Eingliederung der Menschheitsentwicklung in die Naturgeschichte ist die philosophische Anthropologie des 20. Jahrhunderts mit dem Versuch begegnet, die Sonderstellung des Menschen in seiner Weltoffenheit zu begründen. In der Gegenwart basiert sowohl die evolutionäre als auch die neuere philosophische Anthropologie zunehmend auf dem Paradigma der Verkörperung. Einsichten der embodied cognitive science aufgreifend fragt der vorliegende Band, inwiefern die spezifische Geistigkeit und Kulturfähigkeit des Menschen in Strukturen seiner Leiblichkeit begründet liegen, die sich evolutionär herausgebildet haben und dabei umgekehrt durch Kultur beeinflusst wurden. Der traditionelle dualistische Gegensatz von Natur und Kultur wird zugunsten der Theorie eines Prozesses überwunden, in dem Geist und Körper ineinander verschränkt sind und sich wechselseitig konstituieren.InhaltsübersichtGregor Etzelmüller/Christian Tewes: Introduction 1. Philosophical Concepts and Perspectives of Embodiment Christian Tewes: Introduction – Mog Stapleton: Leaky Levels and the Case for Proper Embodiment – Christian Tewes: Embodied Habitual Memory Formation: Enacted or Extended? – Karim Zahidi/Erik Myin: Radically Enactive Numerical Cognition – Christian Spahn: Beyond Dualism? The Implications of Evolutionary Theory for an Anthropological Determination of Human Being 2. The Embodied Evolution of Symbolic Competence Magnus Schlette: Introduction – Thomas Fuchs: The Embodied Development of Language – Terrence Deacon: On Human (Symbolic) Nature: How the Word Became Flesh – Jordan Zlatev: Preconditions in Human Embodiment for the Evolution of Symbolic Communication – Matthias Jung: Stages of Embodied Articulation 3. Embodiment as a Bridging Concept for Evolutionary and Historical Anthropology Alexander Massmann: Introduction – Gregor Etzelmüller: The Lived Body as the Tipping Point Between an Evolutionary and a Historical Anthropology – Eve-Marie Engels: The Roots of Human Morals and Culture in Pre-Human Sympathy. Charles Darwin's Natural and Cultural History of Morals – Christoph Wulf: The Creation of Body Knowledge in Mimetic Processes – Annette Weissenrieder: »It Proceeded from the Entrance of a Demon into the Man«. Epileptic Seizures in Ancient Medical Texts and the New Testament 4. The Mutual Intertwinement of Nature and Culture Miriam Haidle: Introduction – Lambros Malafouris: On Human Becoming and Incompleteness: A Material Engagement Approach to the Study of Embodiment in Evolution and Culture – Duilio Garofoli: Metaplasticit- ies: Material Engagement Meets Mutational Enhancement – Shaun Gallagher/Tailer G. Ransom: Artifacting Minds: Material Engagement Theory and Joint Action – Wolfgang Welsch: Bodily Changes during the Protocultural Period and Their Ongoing Impact on Culture